Performance analysis of 3G-UMTS WDM-RoF links - Almeida, Carlos; Lima, Mario; Teixeira, Antonio (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
In this paper, we analyze the impact of using directly modulated lasers and low cost optical amplifiers to propagate 3G-UMTS radio signals over fiber links. First, we perform a simulation study to identify the main impairments in such systems, and then complement the work with laboratory experiments in order to confirm the results and optimize our low cost radio over fiber system.
Optica Applicata, Vol. 40, 2010, nr 4, s. 773-789
Keywords: optyka; radio over fiber (RoF); passive optical networks (PON); wavelength division multiplexing (WDM); UMTS; SOA